Inclusive Governance Pada Pengelolaan Sagu di Kabupaten Kepulauan Meranti - Wina Hariska Putri; Dedi Kusuma Habibie (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Riau, 2022)
Sago is the largest plantation product in the Meranti Islands District, which has the potential as a center for sago cultivation as well as a center for sago consumption. The government has included the private sector, namely PT. National Sago Prima (NSP). And people who have managed sago for generations. The purpose of inclusive governance research on sago management in Meranti Islands District is to find out how inclusive governance is in sago management and analyze what are the inhibiting factors for inclusive governance in sago management in Meranti Islands District. In this study using descriptive qualitative research methods, with data collection techniques through observation, interviews, and documentation. The results of this study are inclusive governance in the management on sago in the Meranti Islands District has not been implemented optimally, because of the lack of transparency from the government to the actors involved. And also some inhibiting factors, namely the lack of promotion from the government and the lack of public awareness of the Meranti Islands District.